The Determinants Perception Of Male Sex With Man (Msm) Concerning The Utilization Of VCT (Voluntary Counselling And Testing) HIV / AIDS In Dili Municipality, Timor-Leste - Ade Irma Suryani; Maria Margaret San Sao (Jurnal Ilmu Kesehatan, 2021)
Background and objectives: The spread of HIV / AIDS is still a major worrying problem at this time, not a single country in the world is free from HIV / AIDS. WHO has set a target of 90-90-90 which is expected that by 2020, 90% of people living with HIV will know their status, 90% of all people diagnosed with HIV will receive continuous antiretroviral treatment and 90% of all people who receive antiretroviral treatment obtains HIV viral suppression. The Government of Timor-Leste in its efforts to tackle HIV / AIDS in the future by improving coordination between related sectors in the context of implementing AIDS prevention programs with the hope of achieving targets, namely zero new infection, zero AIDS related death and zero discrimination. This study aims to determine the determinants of the perception of MSM in the use of VCT. Methods: This study used a cross-sectional analytic survey design with men having sex with men (MSM) aged ≥ 18 years as respondents. The study was conducted in Dili Municipality, Timor-Leste. The sample was selected using the convenient sampling method with a total of 150 respondents. Data collected by interview method. Data analysis was performed using logistic regression to determine the Adjusted Odd Ratio of each variable. Results: The results showed that respondents who had tested in the last 1 year were 64.7% and respondents who had never tested in the last 1 year were 35.3%. The results of multivariate analysis with logistic regression showed that the variables associated with VCT utilization were perceived vulnerability (AOR = 14.761; 95% CI = 1.976-110.242; p = 0.009) and information sources (AOR = 0.038; 95% CI = 0.005-0.284; p = 0.001). Conclusion: Perceptions of vulnerability and sources of information are related to the use of VCT in MSM. So it is hoped that health workers will collaborate with NGO administrators to be more active in educating MSM regarding the importance of using VCT through VCT mobile services, using approaches through online media and direct counseling.